Development Of Multimedia Planting The Concept Of Spacing (Kocah) For Grade IV Students - Putri Novianti; Desy Dwi Riana; Dwi Kameluh Agustina (STIKes Ibnu Sina Ajibarang, 2023)
Based on the analysis of student needs and interviews with teachers, it shows that mathematics learning, especially in fraction material, has not used innovative media and the minimal use of technology-based learning media has caused students to feel bored and less interested. The purpose of this study was to determine the feasibility and readability of KOCAH Multimedia products for learning Mathematics for fraction material. This type of development research is RnD which has been developed by Sugiono with 7 stages. This study used a questionnaire sheet instrument and interview and observation techniques. Based on the results of the validation test by 9 validators, it is known that KOCAH multimedia can conclude the feasibility of the media by obtaining results from material experts of 87.28%, 91.11%, from media experts and 88.33% from linguists. The results of the student readability questionnaire on KOCAH Multimedia obtained a percentage of 96.15% and the results from the teacher readability questionnaire obtained a percentage of 93.41%.